2014
DOI: 10.1590/s0036-46652014000200014
|View full text |Cite
|
Sign up to set email alerts
|

SEROPREVALENCE OF T. cruzi INFECTION IN BLOOD DONORS AND CHAGAS CARDIOMYOPATHY IN PATIENTS FROM THE COAL MINING REGION OF COAHUILA, MEXICO

Abstract: Context and Objective: Chagas disease is considered a worldwide emerging disease; it is endemic in Mexico and the state of Coahuila and is considered of little relevance. The objective of this study was to determine the seroprevalence of T. cruzi infection in blood donors and Chagas cardiomyopathy in patients from the coal mining region of Coahuila, Mexico. Design and Setting: Epidemiological, exploratory and prospective study in a general hospital during the period January to June 2011. Methods: We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
5
0
4
Order By: Relevance
“…Nonetheless, we can put forward several facts that strongly support our suggestion. Firstly, a previous study conducted by our research team showed a seroprevalence of antibodies to T. cruzi in patients with dilated cardiomyopathy to be as high as 21.14% even in areas of low endemicity [13] and these estimates were obtained and confirmed by two different tests [14]. Seroprevalence as such is an estimator at community level and represents some degree of contact with the parasite.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Nonetheless, we can put forward several facts that strongly support our suggestion. Firstly, a previous study conducted by our research team showed a seroprevalence of antibodies to T. cruzi in patients with dilated cardiomyopathy to be as high as 21.14% even in areas of low endemicity [13] and these estimates were obtained and confirmed by two different tests [14]. Seroprevalence as such is an estimator at community level and represents some degree of contact with the parasite.…”
Section: Discussionmentioning
confidence: 72%
“…These two species have been reported to harbor T. cruzi parasites [15]. Thirdly, there are reports suggesting that Chagas disease may actually be present in the state of Coahuila since ancient times [14]. Finally, it is important to highlight the urging need to trained health teams in non-endemic areas, because they are not accustomed to the presence of Chagas disease.…”
Section: Discussionmentioning
confidence: 99%
“…Porque esta infección es potencialmente transmisible por transfusión de hemoderivados, es importante conocer la prevalencia de dicha enfermedad en personas que aún no hayan desarrollado sintomatología debido a la propia historia natural [10] . En Latinoamérica diferentes estudios utilizando pruebas serológicas han encontrado prevalencias entre 0,05% [14] y 0,31% [11] , resultados que son coherentes con lo encontrado en nuestro estudio.…”
Section: Discussionunclassified
“…Diversos estudios han documentado de manera clara las anormalidades electrocardiográficas en pacientes en la fase indeterminada, en pacientes con serologías positivas en bancos de sangre por diversos métodos. Además, han evaluado la evolución ecocardiográfica y progresión a enfermedad cardiaca sintomática, como también la respuesta al tratamiento en la fase indeterminada, evidenciando un efecto positivo del mismo en los distintos reportes [11][12][13][14][15][16][17][18] . El objeto del presente estudio fue evaluar las características clínicas y hallazgos electrocardiográficos como de ecocardiografía en pacientes quienes tenían una serología positiva en el banco de datos de un centro de referencia del sur de Colombia.…”
Section: Introductionunclassified
“…Isolados de T. cruzi associados ao ciclo silvestre começaram apenas recentemente a serem caracterizados com marcadores moleculares (Charles et al, 2013;Herrera et al, 2008Herrera et al, , 2009Lima et al, 2014;Lisboa et al, 2004Lisboa et al, , 2006Lisboa et al, , 2008Lisboa et al, , 2009Marcili et al, 2009a, b, c;Rocha et al, 2013;Roque et al, 2013;Xavier et al, 2012 Gómez-Hernández et al, 2011;Martínez-Tovar et al, 2014;Molina-Garza et al, 2014;Poveda et al, 2014).…”
Section: Clado T Cruziunclassified